The debate on philosophical sufism: Dynamics and dialectics in Aceh - Mukhlis Latif (IBDA` : Jurnal Kajian Islam dan Budaya, 2023)
This research aims to explain the philosophy of tasawuf Hamzah Fansri in Nusantara Islam. The textual research method was employed to interpret the contents in the manuscripts of tasawuf falsafi in Aceh, especially regarding tasawuf falsafi, which Hamzah Fansūrī developed. The study findings confirm that Hamza Fansūrī's philosophical tasawuf thought is "symbolic-comtemplative" and attempts to locate the exploration of the symbols that are highlighted as the essence and substance of the teachings of philosophical tasawuf. There is a misunderstanding about philosophical Sufism, especially by other parties who try to observe and assess the substance of the teachings of philosophical Sufism, which is a natural thing. Criticism of Hamzah Fansurī's philosophical tasawuf thoughts, especially those made by Nūr al-Dīn al-Ranīrī, is commonplace and reasonable in the scientific realm of Islam. However, the accusation of slander and the opinion that Hamzah Fansurī has gone astray and deviated from Islamic principles is something common sense cannot accept. Hamzah Fansurī's thoughts related to Wujudiyah's views are widespread and have not only developed in Aceh. The originality of this study is that it confirms that philosophical Sufism has a symbolic and implicit aspect and characteristics that are difficult to understand. Therefore, if one is trapped in a narrow understanding of symbols, then philosophical Sufism is only a "skin" which is different from the substance or "content" inside.